2021
DOI: 10.21203/rs.3.rs-539712/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Plasma Proteomics of COVID-19 Associated Cardiovascular Complications: Implications for Pathophysiology and Therapeutics

Abstract: Cardiovascular complications are common in COVID-19 and strongly associated with disease severity and mortality. However, the mechanisms driving cardiac injury and failure in COVID-19 are largely unknown. We performed plasma proteomics on 80 COVID-19 patients and controls, grouped according to disease severity and cardiac involvement. Findings were validated in 305 independent COVID-19 patients and investigated in an animal model. Here we show that senescence-associated secretory proteins, markers of biologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 49 publications
0
20
0
Order By: Relevance
“…B.1.351 is 6.5-fold more resistant than wild-type pseudovirus to neutralization by sera from individuals vaccinated with BNT162b2 (ref. 49 ). A significant reduction in the neutralization of B.1.351 by sera from humans or non-human primates vaccinated with mRNA-1273 was also observed 43 .…”
Section: Effects Of Viral Variantsmentioning
confidence: 99%
“…B.1.351 is 6.5-fold more resistant than wild-type pseudovirus to neutralization by sera from individuals vaccinated with BNT162b2 (ref. 49 ). A significant reduction in the neutralization of B.1.351 by sera from humans or non-human primates vaccinated with mRNA-1273 was also observed 43 .…”
Section: Effects Of Viral Variantsmentioning
confidence: 99%
“…Vaccines developed using different strategies were authorized by many countries to contain the infection of SARS-CoV-2. However, there are growing concerns about safety like antibody-dependent enhancement (ADE), the duration of the effective anti-SARS-CoV-2 immune response, and the effectiveness against the mutant viruses [ 4 6 ]. Thus, the anti-SARS-CoV-2 specific drugs are urgently needed, and more drug targets on this deadly virus are waiting to be uncovered.…”
Section: Introductionmentioning
confidence: 99%
“…These factors could affect the identification of a broader range of proteins involved in microthrombi formation and myocardial injury in COVID-19. Indeed, Roh et al 1 found that ADAMTS13 had a significant yet weak negative association with cardiac troponins, a finding that was reproduced in the independent cohort. However, to overcome the limitations from residual confounding and reverse causation, Roh et al 1 conducted an automated 2-sample mendelian randomization to genetically estimate ADAMTS13 protein levels using locus-wide significant Protein Quantitative Trait Loci (pQTLs).…”
mentioning
confidence: 69%
“…In this issue of JACC: Basic to Translational Science , Roh et al 1 conducted a matched case-control study examining the plasma proteome of 80 patients with different severities of COVID-19 disease, including those hospitalized (but not in intensive care units) and individuals requiring intensive care with different degrees of cardiac involvement along with non–COVID-19 controls. A series of unsupervised enriched principal component analyses revealed that protein profiles related to innate cellular inflammation, senescence, and RNA processing had the highest biological relevance and distinguished between those with and without COVID-19.…”
mentioning
confidence: 99%